Biomass production and antibacterial activity of Justicia gendarussa Burm. f. - A valuable Medicinal plant - Sugumaran, P; Kowsalya, N; Karthic, Raju; Seshadri, S (Journal of Tropical Life Science, 2013)
Rooting and biomass production of Justicia gendarussa has been achieved through a hydroponic system of cultivation. The obtained biomass of leaves, stem and root were examined for antibacterial activity against various human pathogenic organisms such as Staphylococcus aureus, Escherichia coli, Shigella sp., Pseudomonas sp. and Klebsiella pneumoniae. Methanolic extract of J. gendarussa root responded against E. coli. The growth of Shigella sp., Pseudomonas sp. and K. pneumonia were inhibited by leaf extract. The maximum inhibition zone against S. aureus was observed in stem extract treatment.